Micropropagation for the production of high quality phytochemicals - Grevenstuk, Tomás (2015)
Plants area source of many valuable secondary metabolites that find a broad field of applications, ranging from the agrochemical to the pharmaceutical industries. Establishing a suitable source for extraction of phytochemicals is, however, not always straightforward. In many instances the production by chemical synthesis is not economically viable due to their complex structures and conservation issues may arise when they are harvested from natural sources. In vitro culture techniques offer an attractive alternative to these issues. Natural grown plants can be replaced by in vitro produced biomass with the advantage that several strategies can be implemented to increase production yields, such as genotype selection, altering growth conditions and use of elicitors, so that the higher investment costs are justified. Also, because plant tissue cultures can be generated on a continuous year-round basis without seasonal constraints, they can guarantee reliable and predictable production levels, which is of great importance for efficient process down-stream. Plant tissue culture techniques offer the possibility of establishing cultures from leaves, stems, roots and meristems, meaning that metabolites produced in specific plant organs can also be prospected. The successful production of a large number of phytochemicals from micropropagated biomass has been reported, and it seems that only in a few cases cultures fail to accumulate compounds of interest. The advantages and the range of possibilities offered by plant tissue culture techniques suggest that these might become a valuable and indispensable tool for the production of phytochemicals. In this work, the example of the prospection of plumbagin from micropropagated D. intermedia plants is described. Plumbagin is a naphthoquinone with potential pharmaceutical applications and results obtained by several hyphenated analytical techniques confirm that an end product with high purity and recoveries can be obtained from in vitro cultured plants. © ISHS 2013.